Globally competitive pesantren education: Strategies and implementation in Pesantren Ar-Rohmah tahfidz Malang - Juliansyah, Juliansyah; Imani, Mohammad Naghi (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The success of pesantren education is not solely due to the amount of resources, but because of its ability to design strategies that are integrated with internal strengths and external opportunities. With an integral education model that combines tahfizh, academic, and dormitory systems, Ar-Rohmah has succeeded in building a strong positioning in the midst of urban Muslim communities who crave quality and relevant education. This research uses a qualitative approach with a case study method, and utilizes strategic analysis such as IE Matrix, and BCG Matrix. The results show that Ar-Rohmah has a number of strengths, such as its flagship tahfizh program and international teaching staff, but also faces operational challenges. Externally, great opportunities come from the increasing interest in tahfizh education, although accompanied by threats from modern corporate-based pesantren. Based on the IE Matrix analysis, Ar-Rohmah is in a concentrated growth strategy position, while the BCG analysis places it as a Cash Cow that requires a repositioning strategy. The strategies implemented include a combination of SO, WO, ST, and WT approaches, such as improving the quality of human resources, strengthening accreditation, improving internal services, and establishing alumni networks. With structured managerial management and the integration of spiritual values, Ar-Rohmah shows that pesantren can become superior educational institutions that are adaptive and competitive in the global arena.